Quantifying the Migration to Zero Trust Architecture: A Framework for Cloud-Based Mobile Network Enterprises - Khalid, Ali (My University, 2025)
The rapid adoption of 5G technology and cloud-based infrastructures has introduced new cybersecurity challenges for mobile network enterprises. Traditional perimeter-based security models are insufficient in addressing modern networks' dynamic and distributed nature. Zero Trust Architecture (ZTA) offers a security paradigm that eliminates implicit trust and enforces continuous verification across network assets. However, the migration process to ZTA in cloud-based mobile network environments presents unique challenges, requiring a structured and adaptable approach. This thesis proposes a comprehensive framework to guide the migration of cloud-based mobile network enterprises toward ZTA. The research identifies key challenges and requirements for Zero Trust adoption, emphasizing the complexities introduced by 5G-specific technologies such as network slicing, multi-access edge computing (MEC), and service-based architecture (SBA). The study presents a structured framework tailored to these challenges, ensuring a seamless transition while maintaining operational efficiency and security integrity. The framework is validated through its application to a theoretical cloud-based 5G network scenario, demonstrating its adaptability and effectiveness. The results highlight the critical processes involved in ZTA migration, including asset classification, segmentation strategies, policy enforcement mechanisms, and continuous monitoring. The proposed framework provides organizations with a strategic roadmap to systematically implement Zero Trust principles, ensuring enhanced security and resilience in dynamic 5G environments.
Keywords: Zero trust Architecture (ZTA), Cloud-Based Mobile Networks, 5G Technology, Cybersecurity, Migration Frameworks, ZTA Migration, Network Slicing, Multi-Access Edge Computing